Identification of Design and Development Needs for Preschool-aged Children’s Educational Bags - Etwin Fibrianie; Dwi Cahyadi (PANGGUNG, 2017)
AbstractBags for students, especially for preschool-aged children have an important role, namely as learning media in the field of education. Attractive and innovative bag designs are highly required to make acceptable and favorable bags for children. This research uses quantitative method. Design and development of educational bags for preschool-aged children were done through the early stages of planning (mind mapping) and of concept development (determining needs identification). The concept development process began with the dissemination of 30 questionnaires to preschool-aged children to identify the consumers’ need for the bags. From the development process, there were three primary needs and 14 target specifications which were then linked in 8 matrices in the chart of a needs-metrics matrix. This research resulted in educational bag designs for preschool-aged children based on need matrix. Keywords: bags, product design, ergonomics, innovation, primary needs, target specification, need matrix. AbstractBags for students, especially for preschool-aged children have an important role, namely as learning media in the field of education. Attractive and innovative bag designs are highly required to make acceptable and favorable bags for children. This research uses quantitative method. Design and development of educational bags for preschool-aged children were done through the early stages of planning (mind mapping) and of concept development (determining needs identification). The concept development process began with the dissemination of 30 questionnaires to preschool-aged children to identify the consumers’ need for the bags. From the development process, there were three primary needs and 14 target specifications which were then linked in 8 matrices in the chart of a needs-metrics matrix. This research resulted in educational bag designs for preschool-aged children based on need matrix. Keywords: bags, product design, ergonomics, innovation, primary needs, target specification, need matrix.